Prinsip Manajemen Pendidikan Islam yang Fleksibel, Efektif, Open-Minded dan Partisipatif Berdasarkan Kajian Al-Quran - Ajril Akmal; Ali Hamdan (An Najah (Jurnal Pendidikan Islam dan Sosial Keagamaan), 2026)
This article aims to analyze the principles of Islamic educational management flexibility, effectiveness, open-mindedness, and participation based on Qur’anic foundations, particularly QS. al-Hajj: 78, QS. al-Kahf: 103–104, QS. an-Nisa: 58, and QS. al-Maidah: 51. This study employs a library research method using a thematic tafsir (maudhu’i) approach and content analysis. The findings show that QS. Al-Hajj: 78 highlights the importance of flexibility and ease in managing educational institutions; QS. Al-Kahf: 103–104 underscores the need for effectiveness to ensure that educational programs generate meaningful outcomes rather than routine yet unproductive activities; QS. An-Nisa: 58 provides a normative basis for trustworthy and participatory leadership; and QS. Al-Maidah: 51 guides institutions to be open-minded yet selective in adopting innovations and establishing collaborations. Integrating these Qur’anic principles demonstrates that Islamic educational management must be adaptive, outcome-oriented, collaborative, and receptive to new ideas while maintaining ethical and spiritual foundations. This study offers a conceptual framework that can serve as a reference for strengthening the governance of Islamic educational institutions, making them more responsive, sustainable, and competitive in addressing contemporary global challenges.